Structural paths of changes in CO2 emissions in the Chinese construction industry. Issue 5 (16th April 2023) - Chen, Jindao; Song, Xiangnan; You, Jianmin
Abstract : The construction industry contributes significantly to CO2 emissions in China. Understanding the changes in construction CO2 emissions is important for mitigating the emissions. This study examined the structural paths of changes in construction CO2 emissions in China during 2002–2017 by using structural path decomposition analysis. The results demonstrate that construction CO2 emissions increased considerably during the periods of 2002–2007, 2007–2012, and 2012–2017. The final demand effect contributed most to the emission increases, followed by the production structure effect and energy intensity effect. The critical paths contributing to the production structure effect were also identified. "Non-metallic mineral products industry→construction industry" was the critical path to the emission increases. On this path, the final demand effect and energy intensity effect were the main drivers. This study's findings can help policymakers better understand the dynamics of construction CO2 emissions and thus formulate effective policies to reduce the emissions.